2014
DOI: 10.1111/bph.12368
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial bioenergetic function by hydrogen sulfide. Part II. Pathophysiological and therapeutic aspects

Abstract: Emerging work demonstrates the dual regulation of mitochondrial function by hydrogen sulfide (H2S), including, at lower concentrations, a stimulatory effect as an electron donor, and, at higher concentrations, an inhibitory effect on cytochrome C oxidase. In the current article, we overview the pathophysiological and therapeutic aspects of these processes. During cellular hypoxia/acidosis, the inhibitory effect of H2S on complex IV is enhanced, which may shift the balance of H2S from protective to deleterious.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
115
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 233 publications
(278 reference statements)
4
115
1
2
Order By: Relevance
“…This increased inhibition has been believed to shift the balance of H 2 S from protective to deleterious. Sepsis has been documented to be associated with an overproduction of H 2 S, whereas, conversely, in other disease states H 2 S levels and H 2 S bioavailability have been shown to be diminished (224).…”
Section: Elementary Aspects Of H 2 S Biologymentioning
confidence: 99%
“…This increased inhibition has been believed to shift the balance of H 2 S from protective to deleterious. Sepsis has been documented to be associated with an overproduction of H 2 S, whereas, conversely, in other disease states H 2 S levels and H 2 S bioavailability have been shown to be diminished (224).…”
Section: Elementary Aspects Of H 2 S Biologymentioning
confidence: 99%
“…We have recently demonstrated that 3-MST activity is inhibited by oxidative stress in vitro and speculated that this may exert adverse effects on cellular homeostasis (20,21). Given the importance of H 2 S as a vasorelaxant (22)(23)(24)(25)(26)(27)(28)(29), proangiogenic agent (27,(30)(31)(32)(33)(34)(35)(36) and mitochondrial/bioenergetic modulator (20,21,35,(37)(38)(39)(40)(41)(42), here we examined whether the 3-MST/H 2 S system plays physiological regulatory roles in endothelial cells. Next, we examined whether a dysfunction of the 3-MST/H 2 S system develops in hyperglycemia/diabetes and tested whether this dysfunction can be corrected by DL-α-lipoic acid (LA), a known antioxidant and 3-MST cofactor (43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%
“…Although referred to as the prototypical CBS inhibitor, the pharmacology of AOAA is complex (78) and not entirely specific. Its mode of action entails an irreversible binding to the prosthetic group PLP in CBS and therefore other PLPdependent enzymes.…”
mentioning
confidence: 99%
“…To see this illustration in color, the reader is referred to the web version of this article at www .liebertpub.com/ars of GOT1 and other essential enzymes in the glutaminolysis pathway have recently been shown to suppress cancer cell metabolism (109). Therefore, we have recently suggested (78) that AOAA may exert its anticancer effects through the simultaneous suppression of the malate/aspartate shuttle, glutaminolysis, and the CBS/H 2 S axis. In effect, through these diverse, but interrelated pharmacological actions in the cancer cell, AOAA can be viewed as an inducer of ''synthetic lethality'' (Fig.…”
mentioning
confidence: 99%